1991
DOI: 10.3382/ps.0702476
|View full text |Cite
|
Sign up to set email alerts
|

Posthatching Changes in the Immunoglobulin A Concentration in the Jejunum and Bile of Turkeys

Abstract: An experiment was conducted to document the age-related changes in IgA concentration in the small intestine of newly hatched turkey poults reared in floor pens and to determine whether infection with stunting syndrome (SS) affects age-related changes. Day-old turkey poults were dose per os with .5 mL of saline carrier (control) or with .5 mL of one of two dilutions (250- or 2.5 x 10(6)-fold) of a "crude" SS-causing inoculum. Inoculation with the 250-fold dilution depressed body weight gain (P less than .01) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The increase in jejunal IgA from 1 to 5 d of age may be partly due to the secretion of biliary IgA into the intestinal tract. In previous research, Piquer (1990) and Piquer et al (1991) reported that IgA concentration in bile decreased markedly from 1 to 9 d of age.…”
Section: Plasma Igg Concentration Of Turkey Poults Injected With LImentioning
confidence: 96%
“…The increase in jejunal IgA from 1 to 5 d of age may be partly due to the secretion of biliary IgA into the intestinal tract. In previous research, Piquer (1990) and Piquer et al (1991) reported that IgA concentration in bile decreased markedly from 1 to 9 d of age.…”
Section: Plasma Igg Concentration Of Turkey Poults Injected With LImentioning
confidence: 96%
“…The immune system plays a vital role in the development of the gastrointestinal tract, helping the intestine to act as a barrier between the environment and the body. However, the immune system of poultry is immature at the time of hatching, and this observation has been confirmed by several reports (Jeurissen et al, 1989;Piquer et al, 1991;Schat and Myers, 1991). Piquer et al (1991) observed a very low concentration of immunoglobulin A in intestine of poults until 9 d after hatch, followed by a marked increase until 29 d of age.…”
Section: Chapter 2 Literature Review Intestinal Development Of the Nsupporting
confidence: 60%
“…Serum immunoglobulin A (IgA), immunoglobulin G (IgG) and immunoglobulin M (IgM) concentrations were determined appropriately with diluted samples by a sandwich ELISA using microtiter plats and specific IgA, IgG and IgM ELISA quantitation kits (Bethyl Laboratories Inc., Montgomery, TX) according to Piquer et al (1991) .…”
Section: Immune-responsementioning
confidence: 99%